2017
DOI: 10.1016/j.msksp.2017.01.012
|View full text |Cite
|
Sign up to set email alerts
|

People's beliefs about the meaning of crepitus in patellofemoral pain and the impact of these beliefs on their behaviour: A qualitative study

Abstract: Background: A feature of patellofemoral pain is joint crepitus. Several

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 22 publications
2
29
1
1
Order By: Relevance
“…Joint noises are a common feature of normal joint movement; 37 however, participants commonly reported distress and confusion at joint noises, often finding healthcare practitioners’ explanations inadequate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Joint noises are a common feature of normal joint movement; 37 however, participants commonly reported distress and confusion at joint noises, often finding healthcare practitioners’ explanations inadequate.…”
Section: Resultsmentioning
confidence: 99%
“…This was in agreement with previous research, which identified negative emotions and inaccurate aetiological beliefs with joint noises in patients with PFP. 37 …”
Section: Resultsmentioning
confidence: 99%
“…Currently there exists limited evidence to indicate that some with PFP have higher levels of catastrophising and poorer patient-reported general mental health than controls [11]. Qualitative research has also found that catastrophic thinking and anxiety related to joint crepitus, a frequent symptom of PFP, may lead to avoidance or modification of activity [12]. These findings indicate that PFP may be more than just a mechanical problem.…”
Section: Introductionmentioning
confidence: 99%
“…We speculate that these findings might be explained by the negative beliefs individuals with knee pain have regarding knee crepitus. 22,24 Many individuals become fearful and insecure of the noise related to crepitus and might end with the belief that their condition is actually worse than it really is. 24 A common concern of patients in the clinical setting is about the meaning and importance of knee crepitus.…”
Section: Discussionmentioning
confidence: 99%
“…23 Despite being associated with the development of knee OA and structural damage, it is unknown whether knee crepitus is indicative of an overall poor clinical presentation, including lower function, strength, quality of life and higher pain. 1 As individuals with knee pain often report negative beliefs regarding crepitus, 22 it is important to investigate the importance of crepitus to the overall clinical presentation of individuals with knee OA. If crepitus is associated with poor function, this information would aid clinicians to potentially identify a clinical finding indicative of OA severity.…”
Section: Introductionmentioning
confidence: 99%